Peningkatan Kapasitas Pengelolaan Keuangan Berbasis Digital pada UMKM di Kota Pare-Pare - Nirwana, Nirwana; Arif, Hermita; Yolanda, Audrey Michelle Wenny; Utami , Rizky; Idris, Muhammad Istiyansyah Ulman; Hamid, Mashur Naufal; Garantjang, Muhammad Fauzan; Alam, Ade Ikhlas Amal; Rispan, Dhiya Pravidya; Arifin, Marcella; Aprilia, Nurhaliza Purnama (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Ministry of Micro, Small and Medium Enterprises (MSME)s in Pare-Pare City face various obstacles in financial management, such as low digital and financial literacy, the use of manual recording systems, difficulties in separating personal and business finances, and low utilization of digital financial applications This community service program aims to increase the capacity of digital-based financial management in Ministry of Micro, Small and Medium Enterprises MSMEs in Pare-Pare City, South Sulawesi. This activity is motivated by the rapid development of digital technology but has not been optimally utilized by MSME players in the city. Through this program, the service team from the Faculty of Economics and Business, Hasanuddin University will provide training and assistance in digital financial management, simple financial reporting, and the use of financial applications to improve operational efficiency and competitiveness of MSMEs. The program implementation method includes seminars on the introduction of digital financial technology, training on the use of financial applications, and assistance in implementing digital financial systems. The output targets of this program include increased understanding and skills of MSME actors in digital-based financial management, scientific publications in reputable national journals, online media publications, and IPR. It is expected that this program can contribute to improving the professionalism of financial management of MSMEs in Pare-Pare City so that they are able to survive and develop in the digital era and support regional economic growth.